Effectiveness of Cognitive Behavior Group Therapy on decreasing perfectionism, increasing positive affect and mental performance in Female Clergies - Rajaeinia, Alireza (International Journal of Education and Cognitive Sciences, 2022)
The study of the mental status of the female clergies’ community is of great importance due to their role in the mental health of the family. The aim of this study was to evaluate the effectiveness of group cognitive-behavioral therapy on reducing perfectionism, increasing positive affect and improving the psychological performance of female clergies The statistical population of this study included all female clergies. The statistical sample also included 32 female clergies who were randomly assigned to experimental and control groups. The sample responded to the Frost Multidimensional Perfectionism Scale (FMPS), the Positive and Negative affect Scale (PANAS) and the Depression, Anxiety and Stress Scale (DASS-42) in the pre-test and post-test stages. The results were analyzed using SPSS-23 software and multivariate analysis of covariance. The results of multivariate analysis of covariance indicated that group cognitive behavioral therapy had a significant effect on research variables and there was a significant difference between the experimental and control groups (P